Responsabilidade social e competitividade :um estudo sobre a influência de práticas sociais na decisão de escolha de um destino turístico - Silva, Ana Patrícia Sousa e (2006)
The work objective was to investigate the influence of social practices social in the choise decision of a tourist destination. For in such a way, a survey with the aid of a questionnaire, was used as being the research instrument. The study used a simple random sample without replacement, due to elements of the population had a equal probability different of zero, to be selected for forming part of the sample. The used collection method of data was personal interview. The data was collected at Augusto Severo International Airport at the moment in which tourists were embarking in return to the residence place or another tourist destination. For determination of sample size, it was considered the tourist who had visited Natal in November and December, 2004, supplied by the Secretariat of Tourism in the RN. The sample for the research was of 403 people. Results showed that the interviewed express the existence of high level of competitiveness in the tourism industry. It was observed that 42.5% of the interviewed believes to exist a very aggressive competition, and 47.5% believed that the competition is aggressive in the tourism industry. 10.4% of the interviewed expressed much interest in knowing about social practices in the tourism industry and 2.8% had not presented any interest in knowing about social practices in the tourism industry. For the interviewed, the travel agency image is a significant item in the choice for a tourist package, because of 35.6% believed that this factor is very important in the choice. 5% of the interviewed only find that little important or that sometimes the travel agency image can be seen as s decisive factor in the tourist package choice